Wyspecjalizowane agencje marketingowe w działalności rynkowej krajowych organizacji politycznych - Sempach, Marek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper tries to identify the role of specialized marketing agencies in the market activities of Polish political parties. It is based on the extensive observations the author carried out with respect to the application of marketing instruments in the political market. The purpose of the text is to demonstrate how political organizations can gain a competitive advantage by permanent cooperation with professional companies offering marketing consulting services. The starting point of these considerations is the concept of Jennifer Lees-Marshment, a researcher into political marketing from New Zealand, who assumes the total market orientation of a modern political organization (Market Oriented Party). According to her, a party should work the way a business does, ceaselessly meeting the needs of its consumer-voters.